Effect of Different Temperatures and Host Plants on the Biology of the Long-Tailed Mealy Bug Pseudococcus longispinus (Targioni and Tozzetti) (Homoptera: Pseudococcidae): Biology of Mealy Bug Effected by Temperature and Host Plant - Raja, Shazia; Gillani, Waseem; Copland, Mike (Biological Sciences - PJSIR, 2011)
Experiments were done to determine the effects of different temperature levels and three host plants namely, Cucurbita moschata (butternut squashes), Solanum tuberosum var. Desiree (red potato), and Solanum tuberosum var. Cara (white potato) on the biology of mealy bug Pseudococcus longispinus (Targioni and Tozzetti). It was found that the temperature had a significant effect on the development period of both male and female mealy bugs. For males the period decreased with increasing temperatures up to 28 °C, but increased thereafter and host plant had no effect, except at 24 °C. All the aspects of females including total pre-adult, prelarviposition, larviposition period, life span, fecundity and sex ratio were affected by the fluctuating temperatures, but host plant produced no effect on fecundity and sex ratio.